2014
DOI: 10.1111/ijpo.239
|View full text |Cite
|
Sign up to set email alerts
|

Independent and combined influence of neonatal and current body composition on academic performance in youth: The UP & DOWN Study

Abstract: Neonatal and current body composition, both independently and combined, may influence academic performance in youth.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
11
0

Year Published

2014
2014
2022
2022

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 23 publications
(14 citation statements)
references
References 37 publications
(56 reference statements)
2
11
0
Order By: Relevance
“…9,10,50 In this study, only among girls, body fat percentage had a direct negative association with AA, supporting the results of Esteban-Cornejo et al, 9 who found that the association of body fat and AA may be stronger among girls than boys. The authors speculated that obesity may affect girls' self-esteem more strongly than boys', explaining the adverse association between body fat and AA.…”
Section: Obesity and Aasupporting
confidence: 89%
See 1 more Smart Citation
“…9,10,50 In this study, only among girls, body fat percentage had a direct negative association with AA, supporting the results of Esteban-Cornejo et al, 9 who found that the association of body fat and AA may be stronger among girls than boys. The authors speculated that obesity may affect girls' self-esteem more strongly than boys', explaining the adverse association between body fat and AA.…”
Section: Obesity and Aasupporting
confidence: 89%
“…5,6 The association of a physically active lifestyle with learning outcomes has also recently received considerable attention. Previous studies have suggested that excessive screen time 7,8 and excess adiposity 9,10 may predict poorer academic achievement (AA), whereas regular PA and higher aerobic fitness 11,12 benefit AA.…”
mentioning
confidence: 99%
“…Before standardisation, the motor fitness score was multiplied by −1, because it is inversely related to physical fitness. Neonatal characteristics, anthropometric measurements and fitness were included because we found that these covariates were associated with academic performance in previous works with the present sample .…”
Section: Methodsmentioning
confidence: 99%
“…The National Health and Nutrition Examination Survey (NHANES) reported that 14.9% of children were overweight and 16.9% of children were obese in year 2011–2012 . Despite a recently reported small decline in the childhood obesity incidence in 2–5 year olds, national obesity rates remain high and are associated with an increased incidence of type‐2 diabetes, hypertension, hyperlipidemia, cancer, psychological issues and death in young adulthood . Because of these issues, investigators have initiated interventions to reduce body weight and prevent excess weight gain among children often based in schools .…”
Section: Introductionmentioning
confidence: 99%